1978
DOI: 10.1097/00132586-197804000-00046
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Local Anaesthetics After Interscalene Brachial Plexus Block

Abstract: Plasma concentrations of local anaesthetic agents have been measured after 40 interscalene brachial plexus blocks in 39 patients, using lignocaine, prilocaine, bupivacaine and etidocaine. Lignocaine produced greater concentrations than prilocaine; and bupivacaine greater concentrations than etidocaine. The addition of adrenaline resulted in much lower concentrations in the case of all four agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…In addition, the results of this study (in which many patients had rheumatoid arthritis) are similar to those found by Wildsmith and colleagues [1] in a much younger and healthier population. There was no evidence to suggest a greater risk of toxicity in patients with rheumatoid disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the results of this study (in which many patients had rheumatoid arthritis) are similar to those found by Wildsmith and colleagues [1] in a much younger and healthier population. There was no evidence to suggest a greater risk of toxicity in patients with rheumatoid disease.…”
Section: Discussionsupporting
confidence: 90%
“…The range of results was wide (as shown in table III), and one patient in the interscalene group developed a peak concentration of 10.94 |ig ml" 1 . The timing of this does not suggest i.v.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prilocaine is hydrolyzed to hydrolyse to o-toluidine (OT) and Npropylalanine by the help of amidases enzymes. The main reason of methaemoglobinemia is taking overdose of prilocaine (exceeding 600 mg in adults or 8 mg kg -1 in children) which increases the concentration of o-toluidine [3][4][5] . In newborn infants, this enzyme, methaemoglobin, is not complete its development.…”
Section: Fig 1: Chemical Structure Of Prilocaine Hclmentioning
confidence: 99%
“…The stock standard solution of prilocaine HCl was prepared and stored at -20 o C under refrigeration. The six standard solutions (3,5,8,10,12, 15 μg/mL) in methanol were prepared by doing required dilutions from stock solution. Three quality control (QC) samples at the concentrations of 5, 8 and 10 μg/mL were prepared from the stock standard solution.…”
Section: Preparation Of the Standard And Quality Controlmentioning
confidence: 99%